Pandangan Imam Mazhab Terhadap Wali Bagi Janda Relvansinya Dengan Kompilasi Hukum Islam Di Indonesia; Studi Komparatif - Muammar Mahdi; Irfan Lewa (Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to find out about the views of the Imam Madhhab towards Guardians for Widows with the Compilation of Islamic Law in Indonesia (Comparative Study). The type of research used is a literature study (Library Research), the object in this research is the View of the Imam Madhhab towards Guardians for Widows in Relation to the Compilation of Islamic Law in Indonesia (Comparative Study) which is based on the Qur'an and Hadith. Where guardianship is part of Islamic law which is one of the pillars in marriage. In the description, there are differences of opinion among the mujtahids regarding guardianship as a pillar of marriage. There are several things that are considered in guardianship, because the existence of a marriage guardian is a pillar that determines the validity of a marriage, several conditions must be met for a marriage guardian. This research has implications for better understanding how Islamic law regulates marriage with the presence of a marriage guardian through authentic verses and hadiths. and To minimize people who do not know about Guardians for Widowed Women in Marriage. And to explain how the views of the Imam Madhhab towards guardians for widows are related to the Compilation of Islamic Law in Indonesia (Comparative Study).